2003
DOI: 10.1046/j.1472-8206.2003.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and pharmacology of swelling‐sensitive chloride channels, ICl,swell

Abstract: Since several years, the interest for chloride channels and more particularly for the enigmatic swelling-activated chloride channel (I(Cl,swell)) is increasing. Despite its well-characterized electrophysiological properties, the I(Cl,swell) structure and pharmacology are not totally elucidated. These channels are involved in a variety of cell functions, such as cardiac rhythm, cell proliferation and differentiation, cell volume regulation and cell death through apoptosis. This review will consider different as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 188 publications
(247 reference statements)
1
24
0
Order By: Relevance
“…S6) and found that channel activity was blocked in the presence of 100 µM of the potent chloride channel inhibitor, 5-nitro-2-(3-phenylpropylamino)benzoic acid (NPPB), but was restored after washing out the inhibitor as expected [63, 64]. Channel activity was irreversibly blocked after application of 50 µM Gd 3+ , as expected for chloride channels [63,65]. The results indicate the presence of chloride channel proteins in giant proteoliposomes containing purified P-gp and agree with previous studies [64,66,67].…”
Section: Resultsmentioning
confidence: 95%
“…S6) and found that channel activity was blocked in the presence of 100 µM of the potent chloride channel inhibitor, 5-nitro-2-(3-phenylpropylamino)benzoic acid (NPPB), but was restored after washing out the inhibitor as expected [63, 64]. Channel activity was irreversibly blocked after application of 50 µM Gd 3+ , as expected for chloride channels [63,65]. The results indicate the presence of chloride channel proteins in giant proteoliposomes containing purified P-gp and agree with previous studies [64,66,67].…”
Section: Resultsmentioning
confidence: 95%
“…CAAC is the one of very few channels for which a cDNA has not yet been unequivocally identified (d’Anglemont de Tassigny et al, 2003; Eggermont, 2004). To identify the genes encoding CAAC channels in astrocytes, we performed reverse transcriptase polymerase chain reaction (RT-PCR) with primer sets for various CAAC candidate genes such as Cl − channel-Calcium Activated ( CLCA) , Drosophila tweety homolog (Ttyh) , and bestrophin (Best) family genes (Eggermont, 2004; Suzuki and Mizuno, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…A primary role of plasma membrane Cl - channels in non-excitable cells is in the volume-regulatory response to cell volume perturbation [72,73]. It is likely that within the relatively sheltered environment of the host cytoplasm, the parasite is not exposed to significant permutations in osmolarity and that it therefore does not require Cl - channels for this purpose.…”
Section: Discussionmentioning
confidence: 99%